Ophthalmic impairment at 7 years of age in children born very preterm. Issue 3 (21st April 2004) - Cooke, R W I; Foulder-Hughes, L; Newsham, D; Clarke, D
Abstract : Aims: To determine the prevalence of ophthalmic impairments in very preterm compared with term infants, the relation between impairments and cerebral ultrasound appearances and retinopathy, and the correlation with visual perception and motor and cognitive measures. Subjects: 279 children at 7 years of age born before 32 weeks gestation within Liverpool during 1991–92 and attending mainstream schools, and 210 term controls. Methods: Visual acuity was assessed by Snellen chart, and strabismus by the cover test. Stereopsis was determined using the TNO random dot test, and contrast sensitivity using the Cambridge low contrast gratings. Visual and motor abilities were assessed using the Developmental test of motor integration (VMI) and the Movement ABC. Intelligence was measured with the Wechsler intelligence scale for children UK. Perinatal cranial ultrasound and retinopathy data were extracted from clinical records. Results: Children born preterm were significantly more likely to wear glasses, to have poor visual acuity, reduced stereopsis, and strabismus than term controls, but they showed no significant decrease in contrast sensitivity. Ophthalmic impairments were significantly related to poorer scores on the VMI, Movement ABC, and Wechsler IQ tests, but were not significantly related to neonatal cranial ultrasound appearances. Stage 3 retinopathy was related to poorer subsequent acuity. Conclusions: Children born very preterm and without major neurodevelopmental sequelae have an increased prevalence of ophthalmic impairments at primary school age which are associated with visual perceptional, motor, and cognitive defects. The cause may be a generalised abnormality of cortical development rather than perinatally acquired focal lesions of the brain.